Rapid development of tangible interactive appliances: achieving the fidelity/time balance. (6th January 2009) - Gill, Steve; Loudon, Gareth; Woolley, Alex; Hare, Jo; Walker, Darren; Dix, Alan; Ramduny-Ellis, Devina
For some years, the global research community has been developing techniques to rapidly design and develop information appliances. Despite significant advances, many industrial and user interface designers still rely on 2D, software only interactive prototypes, particularly early in the design process when many key decisions are made. A core assumption of many of those tackling this issue is that designers need to be able to make 'quick and dirty' 3D prototypes to evaluate their concepts properly. Some attempts have been made to examine how quick or how dirty the prototyping process can be for software only applications, but to date no one has carried out a similar exercise for 3D information appliance prototypes. This article presents the results of three experiments, presenting empirical data that determines whether tangible prototypes are better than software prototypes and how 'quick and dirty' designers should be prototyping.